Photophysical Properties of Benzoylgermane and para‐Substituted Derivatives: Substituent Effects on Electronic Transitions. Issue 21 (16th September 2016) - Feuerstein, Wolfram; Höfener, Sebastian; Klopper, Wim; Lamparth, Iris; Moszner, Norbert; Barner‐Kowollik, Christopher; Unterreiner, Andreas‐N.
Abstract: In the present study, a selection of basic substitution patterns on benzoyl(trimethyl)germane was investigated using time‐dependent density‐functional theory (TDDFT) to explore the influence on the stability and on the relative order of the lowest excited electronic states. The theoretical results are in agreement with absorption and fluorescence measurements. We show that electron‐withdrawing groups decrease the energetic level of the lowest singlet and triplet state relative to the electron‐pushing systems resulting in red‐shifted radiative transitions (fluorescence). In the first triplet state electron‐withdrawing groups lead to an increased dissociation barrier and a close approach with the singlet ground state before the transition state in the triplet state is reached, favoring radiationless ground‐state recovery. The results are also in good agreement with empirical concepts of organic chemistry, therefore providing simple rules for synthetic strategies towards tuning the excited‐state properties of benzoylgermanes. Abstract : Different substitution patterns on benzoyl(trimethyl)germane can change the excited‐state potential energy surfaces significantly, leading to either dissociation in the excited triplet state (black) or radiationless relaxation to the ground state (red; see picture).